Everything to spend the night : [from A to Z] - Paul, Ann Whitford; Smith, Maggie, 1965- (New York : DK, 1999)
While showing her grandfather all the things, from A to Z, that she has brought with her to spend the night, a little girl suddenly realizes that she forgot one important item.
"A DK Ink book."
"A Melanie Kroupa book"--Added t.p.
1.5
K-3
K-3
Book Links (A.L.A.)
Keywords: Grandfathers -- Fiction; Bedtime -- Fiction; Alphabet; Stories in rhyme; Grandfathers -- Fiction; Bedtime -- Fiction; Alphabet -- Fiction; Stories in rhyme